The observational, cross sectional study to assess quality of life on patient suffering from chronic obstructive pulmonary disease in tertiary care hospital - Joshi, Kavita S.; Amrale, Prasad R.; Ahire, Sagar S. (International Journal of Research in Medical Sciences, 2020)
Background: Chronic obstructive pulmonary disease (COPD) patients often present considerable individual medical burden in their symptoms, limitations, and well-being that complicate medical treatment. Quality of life (QOL) is an important aspect for measuring the impact of chronic diseases. HRQOL measurement facilitates the evaluation of efficacy of medical interventions and also the detection of groups at risk of psychological or behavioural problems. Methods: COPD patient attending the OPD/IPD are screened as per inclusion and exclusion criteria. After obtaining a written informed consent of eligible patient, they were enrolled in the study. QOL of patient is assessed based on a set of questionnaire i.e. COPD Assessment Test™ (CAT). The questionnaire was translated to Hindi and Marathi. Socio demographic variable like age, sex, education occupation and income are also collected. All 8 questions related to health-improvement and management of COPD. CAT scores were given to each question according to the level of impact. Results: In the total score of CAT we observed that there were 2.04% patients with very good QOL, 25.51% with good QOL, 61.22% with moderate QOL and 11.22% with poor QOL. Conclusions: We conclude that the quality of life is moderate in larger number of patient’s population. The most affected domain was the patient’s energy level. The patients enrolled had COPD from long period of time which might have affected their answer because they have been habitual with the difficulties arising from COPD.